Potential Target Analysis of Triptolide Based on Transcriptome-Wide m6A Methylome in Rheumatoid Arthritis - Danping Fan; Danping Fan; Bin Liu; Xiaofeng Gu; Qian Zhang; Qinbin Ye; Xiaoyu Xi; Ya Xia; Qiong Wang; Qiong Wang; Zheng Wang; Bailiang Wang; et al. (Frontiers Media S.A., 2022)
Triptolide (TP), a major active component of the herb Tripterygium wilfordii Hook F (TwHF), has been shown to exert therapeutic potential against rheumatoid arthritis (RA). However, its molecular mechanism of action has not been fully elucidated. This study aimed to analyze the potential target of TP based on the discovery of differentially methylated and expressed genes (DMEGs) in RA using methylated RNA immunoprecipitation sequencing (MeRIP-seq) and RNA sequencing (RNA-seq). Five RA samples and ten control samples were obtained from China-Japan Friendship Hospital. The various levels of m6A methylation and genes expressed in the RA and control groups were compared by MeRIP-seq and RNA-seq. Bioinformatics explorations were also performed to explore the enriched biological roles and paths of the differentially expressed m6A methylation and genes. Molecular networks between TP target proteins and DMEGs were performed using Ingenuity Pathway Analysis (IPA) software. Potential target of TP was determined with Gene Expression Omnibus (GEO) database mining, molecular docking, and in vitro experiment validation. In total, 583 dysregulated m6A peaks, of which 295 were greatly upregulated and 288 were greatly downregulated, were identified. Similarly, 1,570 differentially expressed genes were identified by RNA-seq, including 539 upregulated and 1,031 downregulated genes. According to the deeper joint exploration, the m6A methylation and mRNA expression degrees of 35 genes varied greatly. Molecular networks between TP target proteins and DMEGs were constructed, and the results revealed that tubulin beta-2A chain (TUBB2A), insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3), cytoplasmic dynein 1 intermediate chain 1 (DYNC1I1), and FOS-like 1 (FOSL1) were the most relevant genes that correlated with the target proteins of TP. The results of the GEO database showed that the gene expression of IGF2BP3 was increased in RA synovial tissue and consistent with the trend of our sequencing results of RA PBMCs. Molecular docking and in vitro experiment suggested that TP and IGF2BP3 had a high binding affinity and TP could decrease the mRNA expression of IGF2BP3 in PBMCs and MH7A.This research established a transcriptional map of m6A in RA PBMCs and displayed the hidden association between RNA methylation alterations and associated genes in RA. IGF2BP3 might be a potential therapeutic target of TP during RA treatment.